ANALISIS TINGKAT BERPIKIR KREATIF PESERTA DIDIK MELALUI MODEL PEMBELAJARAN EVERYONE IS A TEACHERE HERE DI KELAS IV SD NEGERI CEBONGAN 2 SALATIGA - Winda Puspita Sari; Jupriyanto Jupriyanto; Sari Yustiana (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2020)
The research focuses on analyzing students' creative thinking levels through the Everyone Is A Teacher Here learning model in grade IV SD Negeri Cebongan 2 Salatiga. The approach used in this research is a qualitative descriptive approach. This type of research is analysis. The instruments used were interviews, observation and documentation. Data analysis techniques use data reduction, data presentation, and data verification or inference. Data validity testing uses technical triangulation and source triangulation. Based on the data analysis of the results of this study it can be concluded that the application of the Everyone Is A Teacher learning model is done to enable students to think creatively by making questions based on the material provided and the level of thinking of students with each other has different ways of creative thinking, so as to be able to spark lots of ideas, lots of ideas, answers and problem solving and be able to provide lots of new knowledge and varied answers.